Africa's Climate Response to Solar Radiation Management With Stratospheric Aerosol. Issue 2 (23rd January 2020) - Pinto, Izidine; Jack, Christopher; Lennard, Christopher; Tilmes, Simone; Odoulami, Romaric C.
Abstract: Anthropogenic warming is projected to increase the magnitude and frequency of extreme events, whose impacts are already being felt in vulnerable regions in sub‐Saharan Africa. Solar radiation management (SRM) has been proposed as an interim measure to offset warming while emissions are reduced; however, the impact of stratospheric SRM on regional climate extremes have not yet been explored, particularly in the Paris agreement context. We investigate the potential impact of SRM on temperature and rainfall means and extremes over sub‐Saharan Africa using simulations from the Geoengineering Large Ensemble. We found SRM significantly reduces temperature means and extremes; however, the effect on precipitation is not as linear. The results should be interpreted with caution as they are particular to this approach of SRM and this modelling experiment. Plain Language Summary: We investigate the potential impact of artificially reducing the amount of sunlight that reaches the Earth's surface on the climate over sub‐Saharan Africa. Human induced warming is projected to increase the magnitude and frequency of extreme events, whose impacts are already being felt in vulnerable regions in sub‐Saharan Africa. Large volcanic eruptions can reduce the global mean temperature. Similarly, the continuous injection of microscopic particles in the upper atmosphere to artificially reduce some of the amount of sunlight reaching the Earth's surface has been proposed as a measure to reduce global temperature while emissions are reduced. The impact of such actions on regional climate extremes is still unclear especially in sub‐Saharan Africa. We analyzed climate model simulations from the Geoengineering Large Ensemble to explore the projected impact of artificial sunlight reduction on climate extremes sub‐Saharan Africa with continued emissions of greenhouse gases. We found that artificially altering the sunlight reduces mean and extreme temperatures, while the effect on rainfall is not as linear and remains uncertain. Key Points: The benefit of SRM as mitigation strategy is larger for temperature than precipitation over Africa There is a regional diversity in the response to SRM SRM is effective over Central and East Africa while changes over West and Southern Africa are mixed